Application of kenaf seed oil-nanostructured lipid carrier to palm-based α-tocopherol cream for photoprotection - Chu, Chee Chin; Azizul Hasan, Zafarizal Aldrin; Tan, Chin Ping; Nyam, Kar Lin (John Wiley & Sons, 2021)
The application of a nanostructured lipid carrier (NLC) to ultraviolet (UV) filter encapsulation was found to enhance its safe use. In this work, a kenaf seed oil-NLC (KSO-NLC) coloaded with 1% diethylamino hydroxybenzoyl hexyl benzoate and 1% ethylhexyl triazone was used as an active ingredient in α-tocopherol cream to develop a photoprotective prototype. It was then subjected to further analysis to determine its physical properties, storage stability, and cytotoxicity. The ratio of KSO-NLC to α-tocopherol cream was optimized based on the sun protection factor (SPF) value using a UV transmittance analyzer. The physical properties of the samples were analyzed, and the amount of α-tocopherol was quantified by ultra-high-performance liquid chromatography. The optimized sample was then evaluated for in vitro antioxidant activities using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid assays. Meanwhile, in vitro cytotoxicity was studied on a normal human dermal fibroblast cell line using thiazolyl blue tetrazolium bromide and cell counting kit-8 assays. The sample of KSO-NLC to α-tocopherol cream in a ratio of 1:2 (N3) showed SPF value >50. Besides, the samples showed microbial stability and sustainable α-tocopherol content upon 12 weeks of storage. The cytotoxicity evaluation of N3 and α-tocopherol cream (N5) showed >100% cell proliferation, which indicated that there is no side effect on the cell growth, while triggering the cell proliferation with the presence of bioactive compounds. Overall, the findings of the study are promising for the development of new sunscreen formulation with the utilization of KSO-NLC and palm-based α-tocopherol cream.